Estimation of Central Venous Pressure by Pacemaker Lead Impedances in Left Ventricular Assist Device Patients. Issue 1 (January 2020) - Imamura, Teruhiko; Moss, Joshua D.; Flatley, Erin; Rodgers, Daniel; Kim, Gene; Raikhelkar, Jayant; Sarswat, Nitasha; Kalantari, Sara; Nguyen, Ann; Juricek, Colleen; Burkhoff, Daniel; Song, Tae; et al.
Abstract : Volume status assessment in left ventricular assist device (LVAD) patients remains challenging. Cardiac resynchronization therapy (CRT) devices are common in LVAD patients, and the impedance across the CRT leads may be associated with hemodynamics and serve as a tool for noninvasive estimation of volume status. Ninety-one sets of measurements including cardiac filling pressures and lead impedances were prospectively obtained during ramp tests from 11 LVAD patients (65.5 ± 9.7 years old; nine male) with CRT devices. Right atrial (RA), right ventricular (RV), and left ventricular (LV) lead impedances were all significantly associated with central venous pressure (CVP) ( p < 0.05). We derived the following equation: estimated CVP = 47.90–(0.086 × RA lead impedance) + (0.013 × RV lead impedance)–(0.020 × LV lead impedance). The estimated CVP had a significant correlation ( r = 0.795) and good agreement with the measured CVP (mean difference –0.14 ± 1.77 mmHg). Applying the above equation on the validation cohort of twenty-one patients also maintained a strong association with measured CVP ( r = 0.705). In conclusion, we have derived a novel equation to estimate CVP using lead impedance measurements. This finding may allow noninvasive monitoring of volume status in LVAD patients. Abstract : Supplemental Digital Content is available in the text.